PENERAPAN BRAIN GYM DALAM PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAM - Rohman, Minahur (Pendidikan Biologi,Universitas Islam Jember, 2013)
Based on information at SMP Negeri 1 Krucil Probolinggo grade VIIA founded some problems related with learning process, those are many student inactive and having science learning product maximal yet. Total of inactive student in the process of learning will be increase in the afternoon, especially in the last time of learning. Based on problems above need to a research about implementation brain gym in science learning. Type of research is class research action. Purpose of this research to know the increasing of learning product and student activity with implementing brain gym on science learning in grade VIIA SMP Negeri 1 Krucil Probolinggo in year 2010/2011. Conclusion of this research are implementing brain gym on learning process able to increase student learning product with average value 82,50, percentage classical comprehensiveness 90,00%, and able to increase student activity.Keywords: brain gym, learning product, student activity